Wongkito.co Campaign Strategy in Gender Equality Issue - Karerek, Karerek; Astuti, Misni; Priambodo, Galih; Nasution, Nurseri Hasnah; Syavira, Rizky Karista (Buana Komunikasi (Jurnal Penelitian dan Studi Ilmu Komunikasi), 2025)
This research aims to see how the campaign strategy on Wongkito.co online media in packaging messages on news channels as a response to the issue of gender equality. This type of qualitative research is descriptive in nature. The subject of the research is the editor-in-chief of Wongkito.co online media. The data used are primary and secondary data. Data collection techniques in this research are observation and interview. The results showed that Wongkito.co online media, as one of the feminist media in Palembang, took part in advocating the theme of gender justice and equality through various rubrics, such as Yundakito, Setara, Katokito, and Bucukito. In practice, Wongkito.co conducts campaigns with the aim of raising the issues of women, children, people with disabilities, minorities, and other vulnerable people. When creating a digital campaign program, there are four steps that must be taken, the problem identification stage, campaign design, campaign implementation, and evaluation. However, Wongkito.co has not implemented the evaluation stage, but only implemented three stages.